Strengthening Religious Education at An-Nizam Private Middle School, Medan - Mahfi, Icha Alfira; Pulungan , Enny Nazrah (FKIP - Universitas Riau, 2025)
This research aims to analyze the strengthening of worship education at An-Nizam Private Junior High School in Medan, focusing on the role of Islamic Religious Education (IRE) teachers and the factors that support or hinder its implementation. The background of this study stems from the importance of shaping students' religious character amid modernization and the moral challenges faced by adolescents. Using a qualitative approach with a phenomenological method, data were collected through observations of religious activities, interviews with teachers, students, and school leaders, as well as documentation of the programs being implemented. The findings reveal that the school has carried out various structured worship programs, such as congregational Dhuha and Dhuhr prayers, Qur’an literacy sessions, Friday prayers for male students, Monday and Thursday voluntary fasting, Mabit (overnight spiritual enrichment), Qur’an memorization reinforcement (murajaah), and religious mentoring. In conclusion, worship education at the school has been implemented effectively due to the strong role of teachers and a supportive environment, although internal challenges from students still require further attention.